Culture making recovering our creative calling - Crouch, Andy. (Downers Grove, Ill. : IVP Books, 2008)
Encourages Christians to contribute to the making of culture, providing examples from church history and contemporary society to demonstrate how culture is created and shaped.
Introduction -- Part I: Culture -- The horizons of the possible -- Cultural worlds -- Teardowns, technology and change -- Cultivation and creation -- Gestures and postures -- Part II: Gospel -- The garden and the city -- Interlude : the primordial story -- The least of the nations -- Jesus as culture maker -- From Pentecost -- To Revelation -- The glorious impossible -- Part III: Calling -- Why we can't change the world -- The traces of God -- Power -- Community -- Grace -- Postscript: Artist in his studio.
Includes bibliographical references (p. [272]-281) and index.
Description based on print version record.
Keywords: Christianity and culture; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books